UTILIZATION OF WASTE MOTOR OILS: ENVIRONMENTAL-AND-ECONOMICAL ASPECT - КУЛИК, М. І. (Man and Environment. Issues of Neoecology, 2015)
Reasons of environment pollution by waste motor oils (WMO) and aspects of environmental safety of WMO are considered. The volume of WMO generation by vehicles is calculated for Kharkiv Oblast (year 2013). Economic losses for environment pollution caused by illegal WMO utilization are calculated. Based on experimental researches, ash and sulphur contents were measured. Comparison of obtained data with M40 masut parameters has shown that WMO ash and sulphur contents are higher than the same parameters for masut. In ash from M100 masut ten heavy metals were identified; concentration of all metals (except Cu) is WMO ash was higher than their concentration in M100 masut ash. It is shown that WMO can be utilized through burning only in case of implementation of set of protective measures.